Development of a multi-rotor vtol uav : structural design and analysis - Lim, Kiat King (2018)
Increasing road congestions in cities raises the need for a new mode of transportation, that is, by air. The overall aim of the project is to design a Vertical Take-off and Landing (VTOL) unmanned aerial vehicle (UAV) that is capable of operating in populated cities. The overall project, consists of two phases: conceptual designing followed by analyzing of the UAV model. In the former phase, eight students worked together to come up with the conceptual design to meet the key characteristic requirements. Thereafter, individual work was done in the analyzing the UAV in different aspects. The design phase consists of market study of various similar UAV, selection of key characteristic and novelties of the UAV. Subsequently, an iterative design process was performed to obtain the parameters for the UAV sizing. The individual scope for this project is to design and analyze the internal structure of the finalized VTOL UAV conceptual design, from the previous phase, using Finite Element Analysis (FEA). Two composite internal structure models were used in this phase, a monocoque and a semi-monocoque structure. The amount of material used were iterated to meet the requirement of not failing during operating condition and achieving the lowest weight possible. The models were then simulated under different operating load conditions. The results from the project gives an insight on the critical areas of the models. Specifically, the root of the canard component and the rotor duct region of the wing component experiences high failure index. The recommendations were to consider redesigning the key components of the UAV, taking into account of the critical regions identified during the analysis. As redesign of the geometry will reduce the stress concentration which is the most effective way of strengthening the critical areas, instead of reinforcing it with more material. It was also shown that adjusting the ply orientation of the composite fiber layup helps to strengthen and reduce the failure index of the models. Advanced optimization techniques could be explored in future works to further improve the model in terms of achieving lower failure index and lower overall weight.